Doublesex Evolution Is Correlated with Social Complexity in Ants. (22nd November 2018) - Jia, Ling-Yi; Chen, Li; Keller, Laurent; Wang, John; Xiao, Jin-Hua; Huang, Da-Wei
Abstract: The Dmrt ( doublesex and mab-3-related transcription factor ) genes are transcription factors crucial for sex determination and sexual differentiation. In some social insects, doublesex ( dsx ) exhibits widespread caste-specific expression across different tissues and developmental stages and has been suggested as a candidate gene for regulating division of labor in social insects. We therefore conducted a molecular evolution analysis of the Dmrt gene family in 20 ants. We found that the insect-specific oligomerization domain of DSX, oligomerization domain 2, was absent in all ants, except for the two phylogenetically basal ant species (Ponerinae), whose social structure and organization resemble the presumed ancestral condition in ants. Phylogenetic reconstruction and selection analysis revealed that dsx evolved faster than the other three members of the Dmrt family. We found evidence for positive selection for dsx in the ant subfamilies with more advanced social organization (Myrmicinae and Formicinae), but not in the Ponerinae. Furthermore, we detected expression of two Dmrt genes, dsx and DMRT11E, in adult ants, and found a clear male-biased expression pattern of dsx in most species for which data are available. Interestingly, we did not detect male-biased expression of dsx in the two ant species that possess a genetic caste determination system. These results possibly suggest an association between the evolution of dsx and social organization as well as reproductive division of labor in ants.